Emerging Nuclear Scenario Pakistan's Concerns and Approaches - Shireen M. Mazari (Policy Perspectives, 2013)
[Major issues on the canvas of the evolving nuclear scenario include the US-favoured discriminatory approach embodied in NPT taking shape of FMCT; the heightened concerns of safety and security of nuclear assets in the wake of Fukushima disaster in Japan as well as the notions of nuclear material/weapons being acquired by non-state-actors; and the whole debate of disarmament. The US managed to get NSG waivers for India in terms of transfer of technology despite India's questionable proliferation record. A full membership of the NSG for India will be very damaging for Pakistan, as NSG works on consensus and India would veto any effort to get exemptions for Pakistan on sensitive nuclear technology. The move to use the UN increasingly as a forum for nuclear issue conflicts is unfortunate because especially in the case of the UNSC, issues become acutely politicised and hard lines are drawn. That non-state actors - primarily terrorists or other groups using violence for their political ends - would want to acquire nuclear weapons is a highly contentious assumption. As to concerns regarding Pakistan's nuclear safety and security, there are well-designed systems and practices in place - with no untoward incident reported so far, as against numerous examples in several other countries. Within the context of South Asia, it is not technology denial that will address the issue of nuclear stability, but political will.]